Interpretation and Use of Penetrometer Data to describe Soil Compaction in Vineyards. - Van Huyssteen, L. (South African Journal of Enology and Viticulture, 2017)
A portable recording penetrometer was used for in situ field measurements of soil strengths in existing experiments with known profile characteristics. The data reported include effects of soil preparation methods, tractor wheel compaction and soil moisture on soil strength, as well as a case study in a productioll'vineyard. The penetrometer proved to be a useful instrument in identifying and quantifying soil compaction problems and the effects of soil management systems in vineyards. The data revealed that serious subsoil compaction can exist which may result in very poor vine performance and even death of the vines.